THE PROBLEMS OF TEACHING MEANS AND METHODS OF SYNTACTIC CONNECTIONS (Education in the 21st Century, 2023)
The teaching of the means and methods of connection in the faculties of philology is carried out in greater depth, examining a number of theoretical issues, and in non-professional faculties the focus is primarily on practical issues. In both cases there is a need to apply methods in the teaching that will ensure the practical application of the knowledge gained. The article presents the approaches to syntactic means and methods that are available in university textbooks and manuals, the teaching methods, the use of which makes the teaching of syntactic means and methods more effective. In particular, when teaching the topic, it is recommended to analyze the connections in the sentences, revealing the means and methods used in each, commenting on their features.
Keywords: Keywords: means and methods of syntactic connections, reconciliation, syntactic control, adjoining, word forms, intonation, the teaching methods.